Cellulose acetate ultrafiltration membranes customized with bio-inspired polydopamine coating and in situ immobilization of silver nanoparticles - Sri Abirami Saraswathi, Meenakshi Sundaram; Rana, Dipak; Alwarappan, Subbiah; Gowrishankar, Shanmugaraj; Kanimozhi, Paramasivam; Nagendran, Alagumalai (New journal of chemistry, 2019)
Herein, we report the effect of modification of cellulose acetate (CA) ultrafiltration (UF) membranes via bioinspired polydopamine (PD) coating followed by in situ immobilization of silver nanoparticles (AgNPs). Such a modification resulted in excellent hydrophilicity, contaminant rejection and minimized both organic fouling and bio-fouling properties. PD coating imparts high surface hydrophilicity and anti-organic fouling properties, whereas the immobilized AgNPs provide excellent anti-biofouling properties to the modified membrane. The immobilization of AgNPs on the CA membrane surface is achieved by simple immersion of the membrane into a silver nitrate solution. The catechol groups present in the membrane facilitate the immobilization of AgNPs via a metal coordination. Leaching tests were also conducted to determine the concentration of the AgNPs in the permeate using Atomic Absorption Spectroscopy (AAS) and we inferred that the concentrations are lower than the usual contaminant limit. Also the contact angle (55.8°), pure water flux (113.1 L m −2 h −1 ) and biofouling experimental results of the modified membranes confirm that there is a significant enhancement in the membrane hydrophilicity, permeability, anti-fouling and anti-biofouling properties when compared to the pristine CA membrane.